(3cJGH GdNjd hGdHjWQIs - (3CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWdj, CHh YHO Gddg fGUQ GdOjf , GHf GNj MRGe GdNWd,J (B250 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdi GdMeO hCgdg hdi GdMeO hCgdg heSJNdUg dfaSg hCMeOg ef NVY dYXeJg s
(3BNQgG (B:s
(3hPdc dCf YQhb ebdeg Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B145s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1417s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs